2020
DOI: 10.3390/su12208643
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Policy Measures Based on Implementation of Digital Technologies in Corrections: Exploratory Study from Slovakia and Beyond

Abstract: Across the world, millions of people are incarcerated every year, while hundreds of thousands of them are released back into their home communities. Despite several alternatives within the criminal justice system, incarceration is still considered as the most natural method of correction. This can lead to different types of unsustainable pathways within a society. Despite the growing importance and increasing use of digital technologies, there are relatively few scientific studies related to the implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…The integration of smart technology necessitates a dynamic and adaptive approach to policymaking [13,57]. Policymakers grapple with the challenge of aligning legal frameworks with the rapid evolution of technology, necessitating continuous updates to address emerging challenges and evolving ethical considerations.…”
Section: Implications Of Smart Technology In Prisonsmentioning
confidence: 99%
“…The integration of smart technology necessitates a dynamic and adaptive approach to policymaking [13,57]. Policymakers grapple with the challenge of aligning legal frameworks with the rapid evolution of technology, necessitating continuous updates to address emerging challenges and evolving ethical considerations.…”
Section: Implications Of Smart Technology In Prisonsmentioning
confidence: 99%
“…In other words, a technology legitimised by managerialism and economist arguments that aim to solve complex social and penal problems without looking deeply at their systemic roots, impossible to solve only with technological artefacts." A short overview of the advantages of EM, based on the use of digital technology in coercion, can be found in the study of Borseková et al (2020). The authors showed that the advantages lead to fewer burdens for taxpayers, less specific costs, offender safety, and maintenance of family and community ties.…”
Section: (A) (B)mentioning
confidence: 99%
“…The authors showed that the advantages lead to fewer burdens for taxpayers, less specific costs, offender safety, and maintenance of family and community ties. Then, the implementation of EM, aimed at lowering criminality through higher responsibility, will also lead to higher public safety "by using more traditional approaches or community supervision, based on probation supervision and parole, and it is hoped that this approach will reduce the number of repeat offenders in the long term" (Borseková et al 2020). The authors also referred to the ratio between the cost of traditional incarceration and cost of E-incarceration (based on the implementation of EM); the 2012 ratio was 4.86 in Austria, 1.46 in the Czech Republic, 3.32 in Denmark, 3.13 in Latvia, and 2.83 in Norway.…”
Section: (A) (B)mentioning
confidence: 99%